CONGESTIVE HEART FAILURE SELF‐MANAGEMENT EDUCATION AND READMISSION AFTER HOSPITALIZATION - Nurul Hidayah; Eka Sakti Wahyuningtyas; Iwan Shalahuddin (Malahayati International Journal of Nursing and Health Science, 2019)
Background: Congestive Heart Failure (CHF) is a condition where the heart can no longer pump blood to the body tissues either to the entire body (systemic circulation) or to the lungs (pulmonary circulation). CHF is a clinical syndrome in patients with structural abnormalities and heart function. Heart function impairment may be a systolic or diastolic function disorder, heart rhythm disturbance, or preload and after load mismatch. This condition can cause death to the patient. Deaths from CHF range from 20-50% per year, in addition CHF is a disease that requires readmission . Frequency of CHF patient readmission  by 45% per year.Purpose: This study aims to analyze the relationship of congestive heart failure self‐management education and readmission after hospitalizationMethods: The study was conducted at ICCU Tidar Magelang hospital with 27 CHF patients who had readmission. The sampling technique was done by consecutive sampling technique. Data analysis in this study using Chi square. The result of statistical test (Chi Square) shows that 2 cells (50%) with expected value <5 means the cells (boxes) whose expected value is below 5 by 50%. The minimum expected value of 2.07 means no expected value <1. Continuity Correction with p = 0,000. Fisher's Exact Test p value = 0,000.Resuts: The results of Symmetric Measure table (correlation test) obtained by the value of Contingency Coefficient (r) = 0.674 with p = 0,000.Conclusion: The conclusion of this statistical test is that there is a correlation between Experience of Self-Management Education (SME)  and readmission  of CHF patients.